ACADEMIC GOVERNANCE AT THE UNIVERSITY SALAH BOUBNIDER CONSTANTINE 3 - Soumia Bentahar; Amirouche Bouchelaghem; Rofia Abada (Universitas Labuhanbatu, 2023)
University governance seems to have undergone many changes, often associated with economic and/or political crises. Until the 1960s, universities were mostly